Collaborative behaviours and social dilemmas during the coronavirus pandemic: does gender matter in the context of Moroccan firms?. (4th November 2022) - Ed-Dafali, Slimane; Kobiyh, Miloudi; Omrane, Amina; Bikhzazen, Nahid
The current COVID-19 pandemic challenges require collective actions aiming at ensuring the preservation of human health by developing a social and an economic resilience. Moreover, experiences show that cooperative and civic behaviours are so credible in a context of solidarity and reciprocity according to a win-win cooperation among all social stakeholders and countries from a micro to a macro - analysis level. The present study explores the choices and decisions made by Moroccan firms through the lens of the game theory and investigates cooperative behaviours occurring during 2020 within social dilemmas. It contributes for a better formalisation of social and behavioural compliance to public policies in times of coronavirus crisis. This research provides then an enhanced understanding of gender differences related to people's behavioural responses to the COVID-19 pandemic and emphasises the importance of adopting individual and collective behaviours required for the coordination of separate actions.